Pengaruh Disiplin Kerja, Pengawasan dan Kompensasi Terhadap Kinerja Pegawai - Husnul Wahyu Lestari; Baiq Ertin Helmida; Ulfiyani Asdiansyuri (Kredibel: Jurnal Ilmiah Manajemen, 2024)
This study aims to examine the of work discipline, supervision and compensation on the performance of employees of thee Office Communication, Informatics anf Statistics of West Nusa Tenggra Province. This study consists 3 independen variables, namely work discipline (X1). Supervision (X2), compensation (X3) and 1 performance dependent variable (Y). The population in this study were 136 employees of the Information, Communication and Statistics Office. The sample in this study was 60 respondents. Data were analyzed using SPSS 25. The results of this study indicate that variables of discipline and compensation have a significant effect partially while the control variable has no significant effect partially, and simultaneously the variables of work discipline, supervision and compensation have a significant effect